Physiological responses during matches and profile of elite Pencack Silat exponents - Aziz, A. R.; Tan, B.; Teh, K. C. (Journal of Sports Science & Medicine, 2002)
This is a descriptive, cross-sectional study describing the physiological responses during competitive matches and profile of elite exponents of an emerging martial art sport, pencak silat. Thirty exponents (21 males and 9 females) were involved in the study. Match responses (i.e. heart rate (HR) throughout match and capillary blood lactate concentration, [La], at pre-match and at the end of every round) were obtained during actual competitive duels. Elite silat exponents` physiological attributes were assessed via anthropometry, vertical jump, isometric grip strength, maximal oxygen uptake, and the Wingate 30 s anaerobic test of the upper and lower body, in the laboratory. The match response data showed that silat competitors` mean HR was > 84% of estimated HR maximum and levels of [La] ranged from 6.7 - 18.7 mMol-1 during matches. This suggests that competitive silat matches are characterised by high aerobic and anaerobic responses. In comparison to elite taekwondo and judo athletes` physiological characteristics, elite silat exponents have lower aerobic fitness and grip strength, but greater explosive leg power (vertical jump). Generally, they also possessed a similar anaerobic capability in the lower but markedly inferior anaerobic capability in the upper body.